Meta Analysis of Effectiveness on Acupuncture Assisted Rehabilitation after Total Knee Arthroplasty - LI Naping; YANG Shaofeng; KUANG Gaoyan; ZENG Fan; TU Duxing; LU Min (康复学报)
ObjectiveTo evaluate the effectiveness of acupuncture as adjuvant therapy for postoperative rehabilitation after total knee arthroplasty (TKA).MethodsThe randomized controlled trials (RCTs) of acupuncture assisted postoperative rehabilitation studies were searched from China National Knowledge Infrastructure (CNKI), Wanfang, VIP, PubMed, Cochrane Library and Web of Science. The Cochrane bias risk assessment tool was used for screening and quality assessment of the included literature, and RevMan 5.3 and Stata 15.1 were used for data analyses.ResultsA total of 11 RCTs with 763 patients were included in final review. Compared with the routine treatment, the meta-analyses indicated that: 1) The resting visual analogue scale (VAS-R) score after TKA in the acupuncture group was significantly decreased [postoperatively 1 d, MD=-0.65, 95%CI (-0.87, -0.42), P<0.000 01; postoperatively 2 d, MD=-0.35, 95%CI (-0.50, -0.21), P<0.000 01]. 2) The passive functional exercises visual analogue scale (VAS-P) score in the acupuncture group was significantly decreased after the surgery [postoperatively 1 d, MD=-1.01, 95%CI (-1.70, -0.33), P=0.004<0.05; postoperatively 2 d, MD=-0.80, 95%CI (-1.43, -0.17), P=0.001<0.05; postoperatively 3 d, MD=-0.90, 95%CI (-1.61, -0.18), P=0.01<0.05; postoperatively 7 d, MD=-0.60, 95%CI (-0.98, -0.21), P=0.002<0.05; postoperatively 14 d, MD=-0.63, 95%CI (-1.07, -0.19), P=0.005<0.05]. 3) The range of motion of the acupuncture group was significantly improved [postoperatively 3 d, SMD=0.47, 95%CI (0.19, 0.75), P=0.001<0.05; postoperatively 7 d, SMD=0.47, 95%CI (0.12, 0.83), P=0.009<0.05; postoperatively 14 d, SMD=0.26, 95%CI (0.00, 0.53), P=0.05≤0.05]. 4) There was significantly better postoperative improvement in the joint function score of the acupuncture group [postoperatively 7 d, SMD=0.71, 95%CI (0.41, 1.01), P<0.000 01; postoperatively 14 d, SMD=0.66, 95%CI (0.36, 0.96), P<0.000 1; at the end of the study, SMD=0.69, 95%CI (0.21, 1.17), P=0.005<0.05]. 5) The incidence of postoperative analgesic adverse reactions was lower in the acupuncture group [vomiting, OR=0.11, 95%CI (0.06, 0.24), P<0.000 01; urinary retention, OR=0.26, 95%CI (0.11, 0.63), P=0.003<0.05].ConclusionThe effectiveness of acupuncture-assisted TKA postoperative rehabilitation is better than that of routine treatment. Due to certain limitations in this study, the research results need to be further verified by more high-quality research.